2001
DOI: 10.1242/dev.128.21.4113
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishcolourlessencodessox10and specifies non-ectomesenchymal neural crest fates

Abstract: Waardenburg-Shah syndrome combines the reduced enteric nervous system characteristic of Hirschsprung’s disease with reduced pigment cell number, although the cell biological basis of the disease is unclear. We have analysed a zebrafish Waardenburg-Shah syndrome model. We show that the colourless gene encodes a sox10 homologue, identify sox10 lesions in mutant alleles and rescue the mutant phenotype by ectopic sox10 expression. Using iontophoretic labelling of neural crest cells, we demonstrate that colourless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 460 publications
(73 citation statements)
references
References 58 publications
5
67
1
Order By: Relevance
“…They did not observe any regeneration impairment in this mutant and concluded that SC are not required for regeneration 36 . This discrepancy with our results could be explained by the fact that foxd3 exhibits a large but incomplete spatiotemporal overlap with sox10 expression 47 . Moreover, the spatiotemporal distribution of the fluorescent proteins in three transgenic lineages, Tg(foxd3:GFP) , Tg(sox10:eGFP), and Tg(sox10: mRFP), shows major differences during early NC development 36 .…”
Section: Discussioncontrasting
confidence: 99%
“…They did not observe any regeneration impairment in this mutant and concluded that SC are not required for regeneration 36 . This discrepancy with our results could be explained by the fact that foxd3 exhibits a large but incomplete spatiotemporal overlap with sox10 expression 47 . Moreover, the spatiotemporal distribution of the fluorescent proteins in three transgenic lineages, Tg(foxd3:GFP) , Tg(sox10:eGFP), and Tg(sox10: mRFP), shows major differences during early NC development 36 .…”
Section: Discussioncontrasting
confidence: 99%
“…Subsequently, one study extended these iontophoretic labelling investigations, confirming both the apparent fate-restriction of many NCCs and the small size of wild-type zebrafish NCC clones. It also characterised a partial failure of NC migration and fate specification in the zebrafish mutants of Sox10 transcription factor ( Dutton et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…2f ). Supporting this conclusion further, at 14 ss, the significant deregulated targets were known components of NC development or differentiation such as sox10 , sox9b , pax3a , and zic1 37 40 (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 53%
“…Mutations in these genes also affect craniofacial development in mice and humans 44 – 48 . Moreover, enhancer bound regions showed strong enrichment for binding sites of known regulators of NCC development such as Foxo1, Sox10, and Hoxa11 37 , 42 , 49 , 50 . To assess whether the binding of Satb2 influences gene expression, we compared corresponding transcript levels between wild-type and satb2 mutants.…”
Section: Resultsmentioning
confidence: 99%